Diversity and characterization of bacteria associated with the deep-sea hydrothermal vent crab Austinograea sp. comparing with those of two shallow-water crabs by 16S ribosomal DNA analysis. - Na Zhang; Chengwen Song; Minxiao Wang; Yuan Liu; Min Hui; Zhaoxia Cui (PLoS ONE, 2017)
For deep-sea hydrothermal vent crabs, recent investigations have revealed some epibiotic bacteria, but no study has described the bacterial community associated with the gill and intestine. In this study, the microbiota attached to the gill and intestine of the hydrothermal vent crab Austinograea sp. and two shallow-water crab species (Eriocheir sinensis and Portunus trituberculatus) were compared by high-throughput sequencing of 16S rDNA genes. The highest and lowest diversity in bacterial communities were observed in the gill and intestine of Austinograea sp., respectively. Non-metric multidimensional scaling (NMDS) analysis indicated that Austinograea sp. harbored a distinct microbial community. Operational taxonomic units (OTUs) for phylum Fusobacteria, class Epsilonproteobacteria, and genera Leucothrix, Polaribacter, Fusibacter, etc. were dominant in Austinograea sp. Of these, Leucothrix, Sulfurospirillum, and Arcobacter may be involved in oxidizing reduced sulfur compounds and sulfur metabolism; Marinomonas, Polaribacter adapted to the low temperature, and Fusibacter and Psychrilyobacter may survive well under hypoxic conditions. Bacteria commonly present in seawater were dominant in the gill, whereas anaerobic bacteria showed strikingly high abundance in the intestine. Interestingly, Firmicutes and Epsilonproteobacteria may complement each other in Austinograea sp., forming an internal environment. The diversified microbial community of Austinograea sp. reveals adaptation to the hydrothermal vent environment.